2010
DOI: 10.1002/ijc.25307
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis suppressor function of NM23‐H1 requires its 3′‐5′ exonuclease activity

Abstract: The metastasis suppressor NM23-H1 possesses 3 enzymatic activities in vitro, a nucleoside diphosphate kinase (NDPK), a protein histidine kinase and a more recently characterized 3 0 -5 0 exonuclease. Although the histidine kinase has been implicated in suppression of motility in breast carcinoma cell lines, potential relevance of the NDPK and 3 0 -5 0 exonuclease to metastasis suppressor function has not been addressed in detail. To this end, site-directed mutagenesis and biochemical analyses of bacterially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 33 publications
5
69
0
Order By: Relevance
“…The 3'-5' exonuclease are critical for maintenance of genomic stability through DNA repair, replication and recombination (Zhang et al, 2011). The loss of Nm23-H1 expression and its cognate 3'-5' exonuclease activity may be conceive to promote genomic instability and malignant progression.…”
Section: The Metastasis Suppressor Nm23-h1 Possesses 3'-5' Exonucleasmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3'-5' exonuclease are critical for maintenance of genomic stability through DNA repair, replication and recombination (Zhang et al, 2011). The loss of Nm23-H1 expression and its cognate 3'-5' exonuclease activity may be conceive to promote genomic instability and malignant progression.…”
Section: The Metastasis Suppressor Nm23-h1 Possesses 3'-5' Exonucleasmentioning
confidence: 99%
“…The 3'-5' exonucleases and NDPK activities of Nm23-H1 is required for metastasis suppressor function. Zhang and his co-workers reported that human melanoma cell lines, 1205LU which metastasizes to the lungs with high penetrance in rodent experimental model of metastasis is deficient in the expression of both Nm23-H1 and Nm23-H2 protein isofoms (Zhang et al, 2011). The wild type Nm23-H1 inhibits motility and invasion capacity and also all mutant animals exhibited normal motility and invasion suppressing activity indicating that none of the activities (NDPK, hisK, and 3'-5' exonuclease) involves to these phenotype in the 1205LU melanoma cell lines.…”
Section: The Metastasis Suppressor Nm23-h1 Possesses 3'-5' Exonucleasmentioning
confidence: 99%
“…As discussed by Kaetzel et al 2014, Nme1 apparently increases genetic stability in melanoma, possibly by a 3′-5′ exonuclease activity as well as NTP fueling to DNA polymerases. In line with this interpretation, Nme1 promoted the repair of UV-induced DNA damage to limit melanoma formation (Jarrett et al 2011;Yang et al 2009;Zhang et al 2011).…”
Section: Nme1 As Metastasis Suppressormentioning
confidence: 56%
“…These multiple functions assigned to the NM23 family of proteins have thus far been difficult to reconcile because the exact cellular function of NM23 has remained unclear. However, beyond nucleoside diphosphate kinase activity several other molecular activities have been linked to NDPKs, such as histidine-dependent protein kinase (histidine phosphotransferase) [18,19] and nuclease activity [20,21], as well as lipid bilayer binding [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%